METHODOLOGY OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE TO A MULTILINGUAL AUDIENCE (Universal International Scientific Journal, 2026)
the article examines the specific features of teaching Russian as a foreign language(RFL) in a multilingual classroom. It analyzes methodological approaches, the challenges ofinterference from students’ native languages, the role of intercultural communication, as well asmodern didactic solutions aimed at improving the effectiveness of instruction. Practical examples oftasks and teaching techniques used in multicultural groups are also presented.
Keywords: russian as a Foreign Language; multilingualism; intercultural communication